2012
DOI: 10.1515/jpm-2012-0102
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of successful breastfeeding initiation in healthy term singletons: a Swiss university hospital observational study

Abstract: Aims: Breastfeeding significantly benefits mothers and infants. We aimed to identify the determinants of its successful initiation. Methods: A retrospective study of 1893 mothers delivering healthy term singletons at a Swiss university hospital from 1/2008 to 3/2009 determined the associations between multiple breastfeeding and early postpartum parameters by univariate and multiple regression analysis. Results: Multiparity was associated with nursing exclusively at the breast at discharge (P < 0.001), less use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
7
21
0
4
Order By: Relevance
“…It has been noted that first time mothers have a high use of EDA [14], and studies show that EDA can affect the infant in a way that postpones the first breastfeeding session [21,22]. The borderline association in the multivariate analysis between a higher maternal BMI and EBF < two months postpartum is in line with previous studies [9,10]. Subjective emotional distress was independently associated with EBF < two months postpartum.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It has been noted that first time mothers have a high use of EDA [14], and studies show that EDA can affect the infant in a way that postpones the first breastfeeding session [21,22]. The borderline association in the multivariate analysis between a higher maternal BMI and EBF < two months postpartum is in line with previous studies [9,10]. Subjective emotional distress was independently associated with EBF < two months postpartum.…”
Section: Discussionsupporting
confidence: 84%
“…Compared to vaginal birth, cesarean section includes several aspects that can affect breastfeeding rates, such as anesthesia [10], and separation [24], between mother and newborn. In Uppsala University Hospital, the newborn is taken out of the operating theatre as a routine, for observation and assessment, and when the mother is under observation postoperatively, the separation is extended, and the newborn will be cared for by the mother’s partner in the maternity ward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with findings from other studies, women who experienced a birth with more intervention (induction, general or epidural/spinal analgesia, instrumental, or cesarean) were also more likely to have infants who were supplemented . These factors are all interrelated and are likely to result in delayed initial feeding or reduced early skin‐to‐skin contact, both of which significantly affect the establishment of breastfeeding . Current guidelines in NSW are aimed at reducing interventions in labor and birth, and have the potential to be associated with improved breastfeeding rates.…”
Section: Discussionsupporting
confidence: 77%
“…Traditional maternal factors that have favoured breastfeeding have been a higher level of education, increasing age, nonsmoking status, normal weight, multiparity and avoiding infant formula supplementation in the first few days after birth (6,19,21). A Swiss study also revealed an association between nipple soreness and pacifier use with nonexclusive breastfeeding at the time of hospital discharge (22). In addition, other factors previously shown to be associated with breastfeeding cessation have been the mother's perception of the father's attitude towards breastfeeding, uncertainty regarding the quantity of breast milk and returning to work (23,24).…”
Section: Discussionmentioning
confidence: 95%